Development and validation of a comprehensive early risk prediction model for patients with undifferentiated acute chest pain. (June 2022) - Dawson, Luke P.; Andrew, Emily; Nehme, Ziad; Bloom, Jason; Liew, Danny; Cox, Shelley; Anderson, David; Stephenson, Michael; Lefkovits, Jeffrey; Taylor, Andrew J.; Kaye, David; Cullen, Louise; et al.
Abstract: Aims: Existing risk scores for undifferentiated chest pain focus on excluding coronary events and do not represent a comprehensive risk assessment if an alternate serious diagnosis is present. This study aimed to develop and validate an all-inclusive risk prediction model among patients with undifferentiated chest pain. Methods: We developed and validated a multivariable logistic regression model for a composite measure of early all-inclusive risk (defined as hospital admission excluding a discharge diagnosis of non-specific pain, 30-day all-cause mortality, or 30-day myocardial infarction [MI]) among adults assessed by emergency medical services (EMS) for non-traumatic chest pain using a large population-based cohort (January 2015 to June 2019). The cohort was randomly divided into development (146, 507 patients [70%]) and validation (62, 788 patients [30%]) cohorts. Results: The composite outcome occurred in 28.4%, comprising hospital admission in 27.7%, mortality within 30-days in 1.8%, and MI within 30-days in 0.4%. The Early Chest pain Admission, MI, and Mortality (ECAMM) risk model was developed, demonstrating good discrimination in the development (C-statistic 0.775, 95% CI 0.772–0.777) and validation cohorts (C-statistic 0.765, 95% CI 0.761–0.769) with excellent calibration. Discriminatory performance for the composite outcome and individual components was higher than existing scores commonly used in undifferentiated chest pain risk stratification. Conclusions: The ECAMM risk score model can be used as an all-inclusive risk stratification assessment of patients with non-traumatic chest pain without the limitation of a single diagnostic outcome. This model could be clinically useful to help guide decisions surrounding the need for non-coronary investigations and safety of early discharge.